2021
DOI: 10.1177/0309324720984930
|View full text |Cite
|
Sign up to set email alerts
|

In-situ EBSD study of the degradation behavior in a type 316 Austenitic Stainless Steel during plastic deformation

Abstract: Type 316 steels have been heavily utilized as the structural material in many construction equipment and infrastructures. This paper reports the characterization of degradation in 316 austenitic stainless steel during the plastic deformation. The in-situ EBSD results revealed that, with the increase of plastic strain, the band contrast (BC) value progressively decreased in both grain and grain boundaries, and the target surface becomes uneven after the plastic tensile, which indicates that the increase of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Tensile stress on the specimen reduces its cross-sectional area while increasing axial stress and strain. As a result, the grains within the material deform and restructure, leading to the generation of new grains and a decrease in mean grain size [ 37 ]. However, the ASTM grain size number of the fatigue fracture specimen was higher than the one of the as-received MIM SS 316L specimen as shown in Figure 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Tensile stress on the specimen reduces its cross-sectional area while increasing axial stress and strain. As a result, the grains within the material deform and restructure, leading to the generation of new grains and a decrease in mean grain size [ 37 ]. However, the ASTM grain size number of the fatigue fracture specimen was higher than the one of the as-received MIM SS 316L specimen as shown in Figure 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al [26] found that the geometrically necessary dislocation density (ρ GND ) increased significantly with increasing plastic strain. The relationship between the ρ GND and the local misorientation is shown as follows [27,28].…”
Section: Ebsd Analysismentioning
confidence: 99%